IMPLEMENTASI KONSEP ARSITEKTUR REGENERATIF PADA PERANCANGAN PLASTIC LEARNING AND RECYCLING CENTER DI KAWASAN PINTU AIR MANGGARAI, JAKARTA - Shevira Zahra Rahmatunissa; Irene Syona Darmady (Jurusan Arsitektur dan Perencanaan, 2026)
The plastic waste crisis has become an increasingly urgent environmental phenomenon, not only causing water and soil pollution but also impacting public health through microplastics and hazardous emissions. This condition is highly visible in Jakarta, particularly in the Manggarai Sluice Gate area, which during the rainy season receives 600 to 700 tons of waste per day, 30% to 35% of which consists of single-use plastics. A crucial spatial issue is the lack of integrated local waste processing in densely populated areas, such that waste is only transported to landfills without providing added value or restoration for the river ecosystem. The objective of this research and design is to formulate a regenerative architecture-based solution through the development of the Plastic Learning and Recycling Center (PLRC) as a facility that functions for processing, education, and community empowerment. For the sub-study, the focus is placed on the principles of regenerative architecture and circular economy which emphasize a closed-loop system in the form of a plastic-to-energy-to-material process. The research method uses a qualitative approach with field observations, interviews, literature review, site analysis, precedent studies, and the synthesis of massing concepts. The research results formulate a design with a vertical zoning system that separates technical areas and education zones. The novelty of the results shows innovation in combining technical, educational, social, and ecological functionalities within a single regenerative architecture facility. Thus, the PLRC in Manggarai becomes a design prototype that not only suppresses plastic pollution but also contributes to the restoration of urban ecosystems as well as strengthening community capacity toward sustainability. Keywords: ecosystem; gasification; plastic; pyrolysis; regenerative Abstrak Krisis sampah plastik telah menjadi fenomena lingkungan yang semakin mendesak, tidak hanya menyebabkan pencemaran air dan tanah, tetapi juga berdampak pada kesehatan masyarakat melalui mikroplastik dan emisi berbahaya. Kondisi ini sangat terlihat di Jakarta, khususnya di area Pintu Air Manggarai, yang selama musim hujan menerima 600 hingga 700 ton sampah/hari, 30% hingga 35% di antaranya merupakan plastik sekali pakai. Masalah ruang yang krusial adalah ketiadaan pengolahan sampah lokal yang terintegrasi di kawasan padat penduduk, sehingga sampah hanya diangkut ke TPA tanpa memberikan nilai tambah atau pemulihan bagi ekosistem sungai. Tujuan dari penelitian dan perancangan ini adalah merumuskan solusi berbasis arsitektur regeneratif melalui pembangunan Plastic Learning dan Recycling Center (PLRC) sebagai fasilitas yang berfungsi untuk pengolahan, edukasi, dan pemberdayaan masyarakat. Untuk sub-kajian, fokus dilakukan pada prinsip arsitektur regeneratif serta ekonomi sirkular yang menekankan sistem tertutup (closed loop) berupa proses dari plastic-to-energy-to-material. Metode penelitian menggunakan pendekatan kualitatif dengan observasi lapangan, wawancara, kajian literatur, analisis pada tapak, studi preseden, dan sintesis konsep gubahan massa. Hasil penelitian merumuskan desain dengan sistem zonasi vertikal yang memisahkan area teknis dan zona edukasi. Kebaruan hasil menunjukkan inovasi dalam menggabungkan fungsionalitas teknis, edukatif, sosial, dan ekologis dalam satu fasilitas arsitektur regeneratif. Dengan demikian, PLRC di Manggarai menjadi prototipe desain yang tidak hanya menekan pencemaran plastik, tetapi juga berkontribusi dalam pemulihan ekosistem perkotaan serta memperkuat kapasitas masyarakat menuju keberlanjutan.